Concepts of Strategic Management of Information Technology - Slamet, Cepy; Aedah, Abd Rahman; Muhammad Ali, Ramdhani (IOP Publishing, 2019)
Strategic management of information technology (SMIT) is closely related to many strategical activities involving IT utilization which are coordinated to achieve organizational goals within a competitive business environment. Along with the dynamics of research development to disclose the strategic roles of IT, previous research proposed various models in relation to how IT contributes to organizational success involving different variables. The difference within models raised some eccentricities since they pointed the same endpoint, organizational performance. This study presents a literature review exploring the general concept of SMIT by mapping each identified strategic factor, configuring the intersection, and discussing a collaborated SMIT models. We conclude three outer layers of SMIT concept, that are SMIT establishment or the environment, significant factors, and a combined model.